Some characteristics of organic apiaries in Hungary - Szalai, Dániel (JOURNAL OF LANDSCAPE ECOLOGY, 2008)
Hungary is among the largest honey producers in Europe. Since the demand for safe agricultural products has grown in the last decade Europe-wide, the number of organic beekeepers in Hungary has increased. Organic agricultural production is regulated by the EEC 2092/91 and 1804/99 regulation. Depending on the nectar source (bee-pasture) there has been only minor difference between organic and conventional beekeeping till the 1980’s. After the appearance of the Varroa mite (Varroa destructor) the beekeeping practice changed and divided into organic and so-called conventional. Though the number of organic beekeepers is still relatively low compared to the conventional ones, their achievements and technology are often apprecieated by the non-certified beekeepers as well. A practical approach of the regulation is presented in this paper through the characteristics of the Hungarian organic apiaries.